Model to explain dental visit for children aged 0 to 5: Scoping review of birth cohorts. - Pierre-Jean Berat; Vincent DE Andrade; Nolwenn Regnault; Annabelle Tenenbaum; Sylvie Azogui-Levy (PLoS ONE)
Introduction Health services accessibility is a multidimensional concept. An early-life dental visit could improve child dental health. Through birth cohorts, it is possible to identify health conditions and pathways of exposure that occur earlier in life. The aim of this study is to propose a theorical model to explain the use of dental care for children with primary teeth, based on results from birth cohorts. Method 3 databases were queried: PubMed, Embase and Dentistry & Oral Sciences Source. Eligible articles presented data on children's dental visits, with at least one follow-up visit between birth and the child's 6th birthday and based on birth cohorts. Results We identified 649 articles in biomedical literature databases. After exclusions, we read 136 abstracts, and finally 36 articles in their full length. A total of 22 articles were included in the analysis, from 15 countries on 5 continents. The mains proximal factors for access to dental care for preschool children are related to caregivers' perception of children's oral health and its impacts on quality of life. These perceptions are influenced by the child's oral health, the child's and mother's use of healthcare, and the healthcare organization. Dental fear seems to be another proximal factor. However, family social background seems to be an enabling moderator for dental visits. Conclusion The scoping review allowed us to develop a model that explains dental visits for children aged 0-5 years as a multifactorial process influenced by caregivers' perceptions of the child's oral health, the family's quality of life, and the child's dental anxiety.